The Socialist Youth Union (1957–1976) – Polish Counterpart of Komsomol - Sadowska, Joanna (Respectus Philologicus, 2016)
The political system of the Polish People’s Republic was modelled on the Soviet one. Polish youth organizations had the ambitions of being counterparts of Komsomol: they adopted similar work methods and tried to play a similar role in the country. The obvious differences resulted from the specificity of each country and the differences in the societies. The most deeply rooted in the memory of Poles is the Socialist Youth Union, which, being the most stable, existed for almost 20 years with nearly 1.3 million members in the early 1970s. The Union was closely connected with the Polish United Workers’ Party and it had to accomplish two main kinds of political task: to select and prepare future members of the Party, both ordinary and those in the managerial positions, and to educate the whole young generation. The Party indeed treated the organization as its agency, an office dealing with the affairs of youths. However, non-political activity of the Union (culture, entertainment, tourism, etc.) was much more effective and evaluated more positively. Actually, there was much more falsehood in the Union: many members were almost completely passive and the work was often only simulated.